Options and prospects of underground storage of carbon dioxide in the Slovak Republic - O. Susak, J. Pinka, I. Plučinský (JOURNAL OF HYDROCARBON POWER ENGINEERING, 2018)
This paper describes an overview of particular solutions and approaches to dealing with the issue of carbon dioxide storage options in the Slovak Republic. It also deals with the options of capture and subsequent storage of carbon dioxide in underground geological formations. The Carbon Capture and Storage (CCS) technology, which seems to be very promising in this context, is one of such technologies. Smaller or larger CCS projects are carried out in different countries around the world. This contribution emphasizes the overview of solutions and approaches to the issue of dealing with CO2 and options of its storage in Slovakia. Concept of CO2 storage in deep geological formations has both its supporters and opponents. Global climate changes will likely be a very important factor that could significantly change the life conditions on the Earth.